Analisis penghindaran pajak dalam perspektif Islam: Peran moderasi GCG pada koneksi politik, CSR, dan profitabilitas - Amanda Nurfadillah; Agung Yulianto; Itah Miftahul Ulum (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze the influence of political connections, rent-seeking, and corporate social responsibility (CSR) on corporate tax avoidance behavior, with the results indicating that corporate social responsibility (CSR) acts as a driving factor. Using quantitative methods and panel data regression analysis, this study examines manufacturing companies listed on the Indonesia Stock Exchange during the period from 2021 to 2024. The sample used is specific, resulting in 556 observations from 139 selected companies. Tax avoidance is measured using the Effective Tax Rate (ETR), political ties using a dummy variable, Corporate Social Responsibility (CSR) using the Corporate Social Responsibility Performance Index, and profitability using Return on Assets (ROA), while Corporate Governance (GCG) is represented by the ratio of independent board members. The results of the study indicate that political ties and corporate profitability significantly influence tax avoidance, while corporate social responsibility (CSR) does not have a significant influence on this. Furthermore, good corporate governance (GCG) was found to mitigate the influence of political ties on tax avoidance. According to Islamic teachings, tax avoidance contradicts the principles of justice and integrity.